An analysis of road light intensity on single lane road with lamp pole on curbside edge - Akop, Mohd Zaid; Ishak, Muhamad Saufi; Mansor, Muhd Ridzuan; Md. Saad, Adzni; Azlan, Khairul Azri; Wasbari, Faizil; Noordin, Aminurrashid; Masripan, Nor Azmmi; Salim, Mohd Azli; Abdul Hamid, Nurfaizey; Ab. Majid, Mad Helmi; Maamor, M. H. M.; et al. (Society of Automotive Engineers Malaysia, 2024)
This paper provides an in-depth analysis of light intensity on a single-lane road, where lamp poles are positioned at the curb’sedge. The objective is to assess the distribution of light across the road. The study involves measuring light intensity at various heights and angles from the road surface, utilizing a lux meter. For this purpose, a portable streetlamp was specially designed to measure the light intensity on a single-laneroad. Several factors were considered, including the road’s length, width, the lamp’s height, and the angle at which the light is projected. Based on these parameters, light intensity readings were obtained along a grid line on the road. The findings reveal that light intensity is higher at the beginning and end of thelamp’s reach, with lower intensity levels observed in the middle of the road between lamp posts. This research provides a valuable foundation for city planners and engineers to improve road lighting systems, thereby enhancing safety and efficiency in transportation networks. Additionally, the study evaluates the potential effectiveness of Autonomous Emergency Braking Systems (AEB) in vehicles.